PERBANDINGAN DURASI KONSONAN [F] ANTARA MALOKLUSI ANGLE KELAS I DAN KELAS III DENGAN DIALEK SUNDA (Kajian pada Ikatan Keluarga Pelajar Mahasiswa Jawa Barat Yogyakarta) - , MUHAMAD FIKRI, drg. JCP. Heryumani S., MS., Sp. Ort.(K). ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Classification of malocclusion and dialect are the two factors that affect a personâs speech articulation pattern. Societies with Sundanese dialect are proven difficult to pronounce the consonant [f]. Difference in articulation pattern for the consonant [f] also happens between Angle malocclusion class I and III. This research is conducted to compare the duration of consonant [f] between Angle malocclusion class I and class III in Sundanese dialect. Subjects are the members of Ikatan Keluarga Pelajar Mahasiswa Jawa Barat Yogyakarta which were preferred based on the research criteria, 18 people were chosen with Angle malocclusion class I, and 15 people with Angle malocclusion class III. Measurement of consonant [f] duration in the beginning, middle, and ending of words in reading provided narration was done by Speech Analyzer 3.1. Data acquired from the measurement was analyzed using independent samples t test. Data resulted from the research shows that consonant [f] in the beginning and middle of the word in Angle malocclusion class III is shorter in duration compared to class I, meanwhile duration of consonant [f] in the ending of the word in Angle malocclusion class III is longer than class I. Independent samples t test shows the difference in the durations of consonant [f] is proved insignificant (p > 0.05). Thus conclusion drawn from the research is that there is no significant difference in the duration comparison of consonant [f] in the beginning, middle, and ending of the word between Angle malocclusion class I and class II in Sundanese dialect.